2023
DOI: 10.3390/diagnostics13142429
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Neurosurgery: A State-of-the-Art Review from Past to Future

Jonathan A. Tangsrivimol,
Ethan Schonfeld,
Michael Zhang
et al.

Abstract: In recent years, there has been a significant surge in discussions surrounding artificial intelligence (AI), along with a corresponding increase in its practical applications in various facets of everyday life, including the medical industry. Notably, even in the highly specialized realm of neurosurgery, AI has been utilized for differential diagnosis, pre-operative evaluation, and improving surgical precision. Many of these applications have begun to mitigate risks of intraoperative and postoperative complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…The diagnosis and treatment of spine conditions have advanced with modern technology, and this technology has enabled advances in options for care. Digital radiography, computerized mensuration programs, and precision digitization tools are necessary to aid and reduce human error from both interventions and spine alignment diagnosis [14][15][16][17]. It has previously been shown that radiography mensuration techniques using analog tools such as pencils and protractors are repeatable, reliable, and valid with multiple investigations that show good inter-and intra-examinator agreement [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis and treatment of spine conditions have advanced with modern technology, and this technology has enabled advances in options for care. Digital radiography, computerized mensuration programs, and precision digitization tools are necessary to aid and reduce human error from both interventions and spine alignment diagnosis [14][15][16][17]. It has previously been shown that radiography mensuration techniques using analog tools such as pencils and protractors are repeatable, reliable, and valid with multiple investigations that show good inter-and intra-examinator agreement [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Technological advances in spine pain diagnosis and treatment are necessary to reduce cost, improve outcomes, increase efficiency for the facilities and clinicians as well as reduce poor outcomes that may require additional care [11][12][13]. Technology can make the process of spine condition diagnosis more efficacious [14][15][16]. For example, previously, we presented a machine learning deep convoluted neural network (DCNN or CNN) that demonstrated that computer vision (CV) is superior to human measurement of spine displacements [17].…”
Section: Introductionmentioning
confidence: 99%
“…These systems allow for the reprocessing of imaging data and for better defining, through virtual reality (VR), the relationships between pathological tissue and normal nervous structures [16]. All these data can be integrated in real time with intraoperative navigation systems, and through augmented reality the surgeon can visualize an overlap between the direct intraoperative microscopic view and previously planned 3D visual data with consequent improvement of the intraoperative orientation, and lastly increased precision during the procedure [13,14,16]. Real life and virtual morphological data can therefore be matched to functional information obtained by intraoperative mapping and monitoring, further enhancing intraoperative orientation and preservation of neurological functions [20].…”
Section: D Surgical Simulationsmentioning
confidence: 99%
“…In the management of the pre-surgical and surgical phases, availability of detailed anatomical and functional planning tools allows for the performance of very complex procedures, ensuring an optimal sparing of neurological function [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation